Impelementasi Kurikulum Merdeka Belajar Pada Pembelajaran Projek Penguatan Profil Pelajar Pancasila Di MTsS Madinatul Ilmi Kecamatan Brandan Barat - Layli Muqarramah, Usmaidar, Nurmisda Ramayani (Pusdikra Publishing, 2023)
This study aims to determine the planning of independent learning curriculum in learning projects to strengthen students' Pancasila profiles at MTsS Madinatul Ilmi Brandan District. To find out the process of implementing the self-learning curriculum in learning projects to strengthen students' Pancasila profiles at MTsS Madinatul Ilmi Brandan District. To find out the implementation of the self-learning curriculum in learning projects to strengthen students' Pancasila profiles at MTsS Madinatul Ilmi Brandan District. To obtain the data needed in this research, field research is used, namely by using data collection tools through observation, interviews or structured interviews, and documentation. . The data obtained is then processed and analyzed. In this research, qualitative research with a descriptive approach is used, namely by describing the research results obtained through in-depth interviews with research sources. Research Results Planning is something that is very urgent in every action, because planning is a compass as well as a map in traveling towards actions that are in accordance with the expected goals. As a formal educational institution, MTsS Madinatul Ilmi certainly also has a strong desire to produce the expected graduates. For this reason, MTsS Madinatul Ilmi aims to create graduates who are knowledgeable, morally good and have the spirit of Pancasila. The application of independent learning through the profile of Pancasila students through Islamic Religious Education learning at MTsS Madinatul Ilmi Brandan District, the first is to create a pleasant learning environment. The key to implementing project activities is student involvement in the learning process. In the implementation of the Pancasila Student Profile Strengthening Project, students, educators, and education units must both have sufficient space and opportunities to develop themselves in accordance with the spirit of independent learning. At MTsS Madinatul Ilmi Brandan District, the facilitator always accompanies students and provides a safe room so that students are always comfortable in carrying out the project learning process.